2019
DOI: 10.1038/s41598-019-48553-y
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting signals of cardiovascular health among natriuretic peptides in subjects without heart disease

Abstract: Natriuretic Peptides (NP) are important in maintaining normal cardiac and metabolic status and have been used to predict cardiovascular events. Whether plasma concentrations of NP products within the normal range reflect cardio-metabolic health is unknown. Plasma NTproANP, NTproBNP and NTproCNP and their bioactive counterparts were measured in a random sample of 348 community dwellers aged 49–51 yr without heart disease and associations sought with established vascular risk factors, echocardiographic indices a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 42 publications
4
18
0
Order By: Relevance
“…Although the bio inactive product NTproCNP is not likely to be degraded at source, whether efflux from extracellular fluids is sufficient to affect plasma concentrations is unclear. While difficult to rigorously assess in humans, our findings from veno-arterial sampling across organs 26,27 , and recent findings linking higher values of plasma NTproCNP (and to a lesser extent, CNP) with vascular stress in adults without history of heart disease 5,6 , support the view that vascular endothelial proCNP does contribute to circulating levels in some settings. Furthermore, in endothelial cell-specific CNP knock out mice, plasma CNP is significantly reduced 9,28,29 .…”
Section: Discussionsupporting
confidence: 76%
“…Although the bio inactive product NTproCNP is not likely to be degraded at source, whether efflux from extracellular fluids is sufficient to affect plasma concentrations is unclear. While difficult to rigorously assess in humans, our findings from veno-arterial sampling across organs 26,27 , and recent findings linking higher values of plasma NTproCNP (and to a lesser extent, CNP) with vascular stress in adults without history of heart disease 5,6 , support the view that vascular endothelial proCNP does contribute to circulating levels in some settings. Furthermore, in endothelial cell-specific CNP knock out mice, plasma CNP is significantly reduced 9,28,29 .…”
Section: Discussionsupporting
confidence: 76%
“… Abbreviations: wt, wild-type; cr, creatinine. a Adult reference interval (IQR) aged 50 years [ 34 ]. b Elecsys proBNP II Data Sheet reference interval (IQR) for individuals aged 40–49 years with no known cardiovascular disease.…”
Section: Resultsmentioning
confidence: 99%
“… a Conversion factor of 3.6 (unpublished comparative data) applied to the Elecsys proBNP II result to allow comparison with the Boudin cases 1 and 2 (measured by RIA). b Adult male reference interval (IQR) aged 50 years [ 34 ]. c Childhood male reference interval (IQR) for children aged 10-15 years [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CNP promotes endothelial cell proliferation and nitric oxide synthetase activity in endothelial cells. Prior studies in men and non-pregnant women have shown an association between CNP levels and arterial stiffness/elastance and NO-dependent FMD [ 38 , 39 ]. However, our study, first to investigate the association between plasma CNP and maternal endothelial function as well as systemic hemodynamics, did not reveal any significant correlation between CNP and brachial artery FMD% (a gold standard measure of endothelial function) or systemic hemodynamics including SVRI, which is considered as an indirect measure of vascular tone and endothelial function [ 40 ].…”
Section: Discussionmentioning
confidence: 99%